The strands of the Forest School implementation challenges: A literature review - Dabaja, Ziad F. (PRISM: Casting New Light on Learning, Theory and Practice, 2023)
The literature proposes that Forest School, which is a form of outdoor and environmental education, can improve the children’s overall wellbeing. Yet, the implementation of this promising and distinctive educational concept can be hindered by several barriers. In this paper, I draw on relevant resources to introduce the main obstacles to the implementation of Forest School and the factors that could mitigate them. Four criteria guided the selection of the resources: a) the source, type, and content of the paper, (b) the subject matter, (c) the publication date, and (d) the publication language. The present review of literature yielded five main Forest School implementation challenges encompassing the (1) adults’ risk perceptions and attitudes associated with Forest School outdoor activities; (2) meeting curriculum and stakeholders’ expectations; (3) cost and logistical difficulties; (4) finding an appropriate site and using the facilities, and (5) the administrative work. I then juxtapose these challenges with relevant literature, present various mitigating factors, and introduce some implications of this work for research and practice.